Education and aesthetic treatment of acne-prone skin - Bessa, Vicente Alberto Lima; Lima, Rita de Cássia Borges; Gonçalves, Taciara Queiroz; Sá, Juliana Mendonça Farias de; Silva, Fernanda Almeida da (Seven Editora, 2023)
Objective: To investigate the benefits that cosmetic and educational practices provide to the skin of acne patients. Materials and Methods: the research was a case study composed of six volunteers divided into two groups: G1, who received treatment in the cabin, and G2, who received treatment in the cabin, in addition to a cosmetic acne treatment kit for use in homecare. Results: The study established a comparison between the treatments performed in the cabin and those administered in homecare, focusing on the analysis of their impact on the emotional and behavioral spheres of the participants. The results revealed a notable improvement in the volunteers’ perception of acne, who reported less impact on their daily activities. The study emphasized the relevance of providing authoritative information and guidance on acne and proper skin hygiene, culminating in a significant increase in participants’ knowledge of the condition. The survey found that beliefs related to makeup use and the influence of diet on acne remained relatively unchanged. The levels of satisfaction among the participants were considerable, especially in the group that adhered to the homecare treatment, corroborating the efficacy and acceptance of the cabin and homecare treatments. Conclusion: The treatment in the cabin and homecare was more satisfactory than that performed only in the cabin, although both had positive results. People who participated in the study are shown to be more educated in acne skin care. DOI:https://doi.org/10.56238/sevened2023.004-039